2015
DOI: 10.1111/geb.12302
|View full text |Cite
|
Sign up to set email alerts
|

Forest structure and species traits mediate projected recruitment declines in westernUStree species

Abstract: Aim Determine if differences in the climatic niche between conspecific adult and juvenile trees of the western Unites States vary by species traits and to assess if forest canopies moderate the sensitivity of juvenile trees to climatic variation. Location The western Unites States. Methods Using data from the USDA Forest Inventory and Analysis programme, we compare the distribution of conspecific adult and juvenile trees for 62 western US tree species. We relate demographic niche differences to species traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 56 publications
(69 reference statements)
7
143
1
9
Order By: Relevance
“…Our results also suggest that the effects of climate change on the relative abundances of tree species within forest communities may differ based on competitive environment (also see Dobrowski et al 2015). First, changes in community structure might be most rapid in low-competition environments because growth and the sensitivity of growth to climate are highest in these locations, potentially allowing thermophilic species to increase in abundance more quickly .…”
Section: Joint Effects Of Climate and Competition On Individual-scalementioning
confidence: 60%
See 1 more Smart Citation
“…Our results also suggest that the effects of climate change on the relative abundances of tree species within forest communities may differ based on competitive environment (also see Dobrowski et al 2015). First, changes in community structure might be most rapid in low-competition environments because growth and the sensitivity of growth to climate are highest in these locations, potentially allowing thermophilic species to increase in abundance more quickly .…”
Section: Joint Effects Of Climate and Competition On Individual-scalementioning
confidence: 60%
“…To calculate these variables, we used a Thornthwaite-type water balance model following Lutz et al (2010), an approach considered most appropriate when temperature and precipitation data are available but reliable measures of humidity and wind speed are not (Dingman 2002), as was the case in this study.…”
Section: Climate Datamentioning
confidence: 99%
“…In another study in California, declines in large trees and increased density of small trees with dominance of drought-tolerant oaks correlate with increases in climatic water deficit (47). In the water-limited forests throughout the western United States, lack of seedling regeneration at warmer range margins is more prevalent than expansion along cool margins (48), but forest cover buffers the negative effect of climate warming and drying on recruitment (49).…”
Section: Observing Changes In Plant Communitiesmentioning
confidence: 98%
“…For example, we found that Trientalis occurrence is highly related to overstorey cover rather than topographic microclimate, suggesting that small shifts in climate may have little effect on distribution if overstorey cover does not significantly change, whereas loss of overstorey due to increasingly severe or frequent fires could have much more drastic consequences. Facilitative effects of canopy cover may also explain patterns such as persistence of species with 'cool-adapted' traits through long-term drying trends (Valiente-Banuet et al, 2006) and the positive effect of forest density on tree regeneration niche (Dobrowski et al, 2015). These results also imply that changes in biotic conditions independent of climate could lead to shifts in distribution and abundance that were not predicted by climate-based models.…”
Section: Discussionmentioning
confidence: 95%